Discussion questions of essence ofthe public debt risks and problems of their evaluation in Ukraine - LUBKEY, Nadiia (Scientific journal «World of Finance», 2019)
Introduction. The significant and constantly increasing volume of public debt of Ukraine, its irrational structure, inefficient use of borrowed government loans lead to growth of debt risks and decrease of the state debt sustainability. For a successful debt management we need to apply effective risk management ofpublic debt.Purpose. The aim of this research is to clarify the essence of the public debt risk; to analyze the methodological approaches to their evaluation; to determine the main directions for the risk management of public debt, as well as the ways to improve the current methodology forassessing public debt risk in Ukraine.Results. Based on studies of different approaches to interpreting the essence ofthe public debt risk we have established that risk of public debt caused by the presence ofthe probability the formation of such debt parameters that may have significant negative impact on the socio-economic development ofthe country. Analysis ofthe main approaches to assessing of public debt risks revealed a number of shortcomings in current Ukrainian methodology. The main directions ofpublic debt risk management are: managing the risks associated with large amounts of public debt; debt management risks caused by irrational structure of public debt; managing the risks associated with the rapid growth of the public debt; risk management related to the inefficient use ofgovernment loans.Conclusion. The current methodology for assessing the risks associated with debt management used in Ukraine needs to be improved. In our opinion such methodologies must necessarily contain the indicators of effectiveness of government borrowing.